PO-25 - FATCAT: an observational cohort study investigating fractal dimension (df) as a biomarker of thrombogenicity in cancer associated thrombosis during chemotherapy for lung cancer. Issue 140 (April 2016) - Davies, N.A.; Noble, S.; Harrison, N.K.; Morris, R.H.K.; Evans, P.A.
Abstract : Introduction: Venous thromboembolism (VTE), comprising deep vein thrombosis (DVT) and pulmonary embolism (PE) are common complications in patients with cancer, affecting up to 18% of patients. VTE risk is increased by surgery and disease progression, whilst chemotherapy further increases risk up to 7-fold compared to patients without cancer. VTE contributes significantly to morbidity and mortality in patients with cancer, and is the second most common cause of death. Lung cancer is well established to be high risk for VTE, with up to a 22-fold increase in VTE risk associated with this malignancy, and 12% incidence in a recent study of patients with lung cancer undergoing chemotherapy. Furthermore, platinum based chemotherapy agents used in treatment of lung cancer are further associated with increased VTE risk. Aim: Current risk assessment tools have little value in predicting VTE risk, but prophylactic anticoagulation of patients with cancer increases bleeding incidence and no overall survival benefit. There is therefore a need for a pragmatic test with which assesses coagulation in patients with cancer, and potentially predict VTE risk, leading to personalised management and targeted treatment. We have previously demonstrated that fractal dimension (df) is sensitive to changes in clot microstructure in patients with lung cancer, assessing global coagulation in these patients. Furthermore, df is significantly different in patients with extensive disease (stages 3&4), which conventional laboratory markers failed to identify. Given the increased risk of VTE associated with chemotherapy, FATCAT will aim to assess changes in df in a larger cohort of patients with lung cancer undergoing chemotherapy, quantifying changes in df and relating these to clinical outcome. Materials and Methods: This is a prospective observational cohort study investigating changes in df in patients with lung cancer undergoing chemotherapy. Patients will have a new diagnosis of cytologically or histologically confirmed lung cancer planned for chemotherapy and no history of previous cancer treatment, any thromboembolic / haemostatic disorders or be on anticoagulation. Results: Following a power calculation, 300 patients will be recruited and followed up for 1 year. df, Doppler ultrasonography and standard coagulation markers will be performed on recruitment, at the mid point, and on completion of chemotherapy in line with standard diagnostic procedures i.e. CT scanning. Conclusions: The primary endpoint of the study will be VTE diagnosis, whilst secondary outcomes will determine the change in df during and after treatment with chemotherapy.